THE PINEAPPLE VALUE CHAIN IN MUXÚNGUE AND ITS IMPACT ON THE SOCIOECONOMIC DEVELOPMENT OF MOZAMBIQUE (REMUNOM, 2025)
This study focuses on mapping the pineapple value chain, assessing the agro-ecosystem  managed by the rural communities of Muxúngue, in the District of Chibabava, Sofala  province. The research included a sample of 60 pineapple producers, selected by non probabilistic sampling, using snowball techniques. Questionnaires, interviews and direct  observation were applied, as well as the use of the Value Link tool to map pineapple  production and marketing activities. The results indicated that the producers obtain  seedlings from the community itself, using money or products to exchange. Planting is  simple, with seedlings arranged in rows, maintaining soil sustainability by accumulating the remains of other crops between the rows. Pineapples are sold both wholesale and  retail, to different customers who travel along the N1 in the central region of the  country. Average annual production in the region is around 80,000 tons. The study  highlights the importance of the pineapple value chain for the local economy and offers valuable insights for improving the agricultural management of the fruit.